Maine Coon cats: the lions of the cat kingdom / Noor Azli Affendy Lee - Affendy Lee, Noor Azli (Academy of Language Studies, 2023)
I must admit that I have a fascination for big-sized wild-looking cats. During my free time, I like to research and read on animals online and watch animal-related or wildlife channels on Astro, captivated by their behaviours and habitats. There are a handful of people who would love to have these exotic animals as pets, and I admit that I am one of them. However, knowledge is vital to consider the possibility, appropriateness, and feasibility of owning, raising, or breeding any animal, domestic or wild. Compassion needs to follow suit too. I had been breeding Bengal cats for 7 years (2012-2019); so when I stopped, I was intrigued to get myself a different big-sized domestic cat. My topmost list was the savannah cat, a cross between the serval wildcat and a domestic cat, but a savannah is extremely costly (about RM25,000 then). Then, one of my ex-students suggested for me to get him a Maine Coon cat for his wedding present. I was not that fond of long-haired cats as I do not like cat fur cluttering my house. In addition, I am a lazy person when it comes to cleaning and fur maintenance (grooming), hence the reason I had the short-haired Bengals in the first place. However, I do like challenges and exploring my options. Even though that was a joke on my student’s part, after careful consideration, additional reading on Maine Coon care, and searching the nearest and price-appropriate cat breeder via a Maine Coon group on Facebook, I decided to adopt a female tortoiseshell Maine Coon which I named Hoshi (“star” in Japanese) from a local breeder in Kepala Batas, Penang. When he (my student) did not immediately get married, I ended up getting Hoshi a partner, a male orange Maine Coon from a different local breeder in Kulim, Kedah, which I named him Hikaru (“light” in Japanese). I raised both for 2 years, waiting for my student to tie the knot. However, due to some family matters, I had to give them away to a close friend who continues to take care of them until now. The good news is that Hoshi delivered her first batch of offspring this year on 26 March 2023, during the Ramadhan month. One of her 5 kittens, after completing 3 doses of vaccinations, was given to my ex-student who finally tied the knot on 28 May 2023. Maine Coon cats are known as 'gentle giants' and are the largest domesticated cat breed. They have unique characteristics which differ from other domestic cats. Reaching up to 1.2m in length and weighing between 6 to 8 kgs, the males are bigger than females, and if neutered, they can grow much more. Smooth, silky, medium-long thick fur covers their huge, muscular frame to make these felines look even larger. It is of no surprise that the Maine Coon holds the record for being the world’s longest and largest domestic cat. Hence, they are very popular in cat shows and most photos of very huge cats held by people are Maine Coon cats. They have waterproof coat, with a dense undercoat, firm hair, and bushy tail. One distinctive characteristic is they have big, pointed ears that are tufted at the end. Another notable aspect is most Maine Coons have big feet, almost like they are wearing clown shoes. They are polydactyl cats which means that they have more toes than average cats.